Composition, structure, and level of weed diversity in oil palm plantation in Pagar Merbau Village, Tanjung Morawa, Indonesia - Rama R. Sitinjak (Future Science, 2022)
Weed vegetation growth affects the growth and production of oil palm plants. To control weeds in plantation land, especially by using herbicides or bioherbicides, weed vegetation analysis is needed. This research was conducted to determine the composition, structure, and level of diversity of weeds in oil palm plantations owned by the community of Pagar Merbau village, Tanjung Morawa District. The method used is a descriptive method with sampling technique done by porposive sampling. The results of the analysis showed that weeds found were 7 families, 10 species, and 3153 individuals. Weed species found were: Clidemia hirta, Borreria alata, Mimosa invisa, Setaria barbata, Ageratum conyzoides, Paspalum conjugatum, Ottochloa nodosa, Cyclosorus aridus, Calopogonium mucudoines, Ophioglossum reticulatum. Ottochloa nodosa is a type of weed that has the highest importance value index 66.52% (1323 individuals) and Setaria barbata is a type of weed that has the lowest important value index of 1.00% (4 individuals). Weed diversity index in this oil palm plantation is in the moderate category (H '= 1.3741). The weed control system to be carried out in this oil palm plantation must consider the dosage and types of herbicides and bioherbicides used so that it does not have the potential to reduce the level of diversity of weeds of grass or broadleaf weeds.